WAYS TO ADAPT ASSESSMENT MECHANISMS OF THE FINNISH EDUCATION SYSTEM TO GENERAL SECONDARY EDUCATION IN UZBEKISTAN - Usarov Dilshod Abdurashid ugli (Bright Mind Publishing, 2025)
This article analyzes the key features of the assessment mechanisms in the Finnish education system and their impact on students’ personal development, critical thinking, and creativity. It also explores ways to adapt the Finnish assessment model to Uzbekistan’s general secondary education system, emphasizing the integration of diagnostic, formative, and summative assessment elements and the teacher’s role as a facilitator rather than an evaluator. The findings highlight the practical importance of implementing innovative assessment approaches to enhance student motivation and improve education quality in.
Keywords: Finnish education system, assessment mechanisms, formative assessment, summative assessment, education quality, general secondary education of Uzbekistan.